2019
DOI: 10.3389/fmicb.2019.00639
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Growth Conditions Influence Lettuce Leaf Internalization

Abstract: Human pathogens on plants (HPOP) have evolved complex interactions with their plant host. Stomatal internalization is one such mode of interaction, where bacteria are attracted to stomata and penetrate into the substomatal cavity by a process mediated by chemotaxis. Internalization enables HPOP to evade the hostile environment of the leaf surface and find a protected, nutrient-rich niche within the leaf. Numerous studies have documented attachment and entry of the foodborne pathogens, Salmonella en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Although S. enterica induces plant defense responses ( Meng et al, 2013 ; Garcia and Hirt, 2014 ; Melotto et al, 2014 ; Oblessuc et al, 2020 ), it can still persist for long periods in the leaf apoplast depending on the bacterial strain and the plant genotype ( Wong et al, 2019 ; Jacob and Melotto, 2020 ). Furthermore, recent studies have shown that variations in the S. enterica culturing conditions, such as temperature and nutrients in the medium ( Kroupitski et al, 2019 ), and environmental conditions for the plant cultivation, such as temperature and humidity ( Deblais et al, 2019 ; Jechalke et al, 2019 ; Roy and Melotto, 2019 ), can interfere mainly with the ability of S. enterica to internalize plant tissues. Nevertheless, variations in environmental conditions not only affect the bacterial internalization, which indeed is an important step during bacterial colonization of plants, but also interfere with the outcome of the plant–pathogen interactions and the persistence phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. enterica induces plant defense responses ( Meng et al, 2013 ; Garcia and Hirt, 2014 ; Melotto et al, 2014 ; Oblessuc et al, 2020 ), it can still persist for long periods in the leaf apoplast depending on the bacterial strain and the plant genotype ( Wong et al, 2019 ; Jacob and Melotto, 2020 ). Furthermore, recent studies have shown that variations in the S. enterica culturing conditions, such as temperature and nutrients in the medium ( Kroupitski et al, 2019 ), and environmental conditions for the plant cultivation, such as temperature and humidity ( Deblais et al, 2019 ; Jechalke et al, 2019 ; Roy and Melotto, 2019 ), can interfere mainly with the ability of S. enterica to internalize plant tissues. Nevertheless, variations in environmental conditions not only affect the bacterial internalization, which indeed is an important step during bacterial colonization of plants, but also interfere with the outcome of the plant–pathogen interactions and the persistence phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…An adhesion reduction due to the treatment was observed, with fewer and ungrouped bacterial cells in SH samples (Figure 3b); moreover, in the same samples, Salmonella internalization within stomata was observed. This pathogen can use open stomata as a portal of entry into deeper tissues of the plant host (Kroupitski, Gollop, Belausov, Pinto, & Sela, 2019), and this is believed to be a protection mechanism to evade the hostile environment of the leaf during surface disinfection (Golberg, Kroupitski, Belausov, Pinto, & Sela, 2011). Thus, it is possible that unfavorable conditions created by SH on leaf surface prompted Salmonella internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Inoculation of leaves was performed, essentially as described before (Kroupitski et al, 2009(Kroupitski et al, , 2011(Kroupitski et al, , 2019Golberg et al, 2011), except for the incubation temperature. Briefly, a single tomato leaflet, Arabidopsis leaf, or lettuce piece were each submerged in a single 50-ml sterile polypropylene tube (Labcon, Petaluma, CA) containing 30-ml saline.…”
Section: Inoculation Of Leavesmentioning
confidence: 99%
“…10 8 Salmonella CFU/ml saline. While this high inoculum does not represent real-life conditions, such high inocula were previously used to study Salmonella internalization in vivo (Gu et al, 2011(Gu et al, , 2013a and in vitro (Kroupitski et al, 2009(Kroupitski et al, , 2011(Kroupitski et al, , 2019Golberg et al, 2011). The incubation proceeded for 2 h at 40°C, a temperature that increases stomatal openings in multiple species (Kostaki et al, 2020) to facilitate Salmonella internalization.…”
Section: Inoculation Of Leavesmentioning
confidence: 99%